SEBELAS MODAL AGAR MENJADI GURU YANG DICINTAI OLEH PESERTA DIDIKNYA - Yazidul Busthomi (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Abstract: Becoming a teacher is truly noble work. He is responsible for not only making human children smart in the field of science, but also good moral in this life. A human child who at first did not understand anything, before a teacher was educated to understand life better and know the world. On his shoulders is the duty and responsibility of the future survival of more intelligent and confronting generations. So noble the work of a teacher and how heavy the duties and responsibilities of being a teacher. This is why not everyone can become a successful teacher. Only certain people who have a love for children or students and are highly dedicated to the world of education are able to become a teacher. This is the personality of a teacher who is both teaching and educating in front of his students, the figure of a favorite teacher who is loved by his students. Eleven capital in order to become a teacher that is loved by their students are as follows: 1. Close to students, 2. Build a pleasant, atmosphere, 3. Can act as a second parent, 4. Become friends in learning, 5. Personality is worth emulating, 6. Be affectionate, 7. Patience in teaching, 8. Can make you laugh, 9. Liberator for students, 10. Can be a listener and mediator, 11. Not Arrogant.